Are citizens of Delhi willing to stop using private vehicles for their daily office commute in order to reduce air pollution and related ailments? A protocol for a contingent valuation study - Ray, Shomik; Singh, Ranjana; Pathak, Sukanya (International Journal Of Community Medicine And Public Health, 2022)
Background: Increased vehicular traffic is associated with higher levels of air and noise pollution which in turn causes high morbidity and mortality. Governments, including Delhi have invested high amounts in setting up and running public transport systems in order to rationalize road usage and limit vehicles on road. This study proposes to assess the willingness of the citizens to give up their private vehicles in favor of public transport and will provide specific policy recommendations. Methods: This study will be conducted in Delhi/NCR along the Delhi metro route. A systematic review and cross-sectional community survey will be carried out to meet the study objectives. Data will be captured through computer aided personal interviews (CAPI) using contingent valuation methods (CVM). This study will provide information on the perceptions and attitudes of commuters towards the current public transport system and the economic value placed by them on private transportation and provide an estimate of the welfare gain associated with it. Specific objective wise outputs have been framed. This will be the first study using contingent valuation methods (CVM) in a similar setting in India. Conclusions: The result will provide an evaluation of the public transport system of Delhi NCR from a user perspective. The willingness to pay values will provide a monetary value to the health benefits arising from shift from private to public modes of transport along with workable models of interventions for policy makers.